Composite Materials and Advanced Materials Research. - Kim, Jong Hak; Lau, Alan K. T. (Trans Tech Publications, Limited, 2022)
Selected peer-reviewed extended papers abstracts of which were presented at the 7th International Conference on Composite Materials and Material Engineering (ICCMME), and the 12th International Conference on Advanced Materials Research (ICAMR) Aggregated Book.
Description based upon print version of record.
Settlement Comparison Research in Response to Gravel Columns with Concrete under a Distributed Vertical Dynamic Load
Keywords: Materials -- Congresses.; Composite materials -- Congresses.; Additive Manufacturing.; Alloy.; Biomedical Materials.; Building Materials.; Composite.; Functional Materials.; Materials Forming.; Membrane.; Nanoparticles.; Polymer.; Steel.; Matériaux -- Congrès.; Composites -- Congrès.; Composite materials; Materials; Conference papers and proceedings